Prenatal Exposure to Air Pollution and Immune Thrombocytopenia: A Nationwide Population-Based Cohort Study - Yen, Hsin-Chien; Lin, Chien-Heng; Lin, Ming-Chih; Hsu, Ya-Chi; Lin, Yi-Hsuan (Frontiers in Pediatrics, 2022)
Introduction: Immune thrombocytopenia (ITP) is one of the most common hematologic disorders of childhood. However, its etiology is still unclear. Epidemiological studies have shown that air pollution is a plausible risk factor in stimulation of oxidative stress, induction of inflammation, and onset of autoimmune diseases. The objective of this article is to examine the effects of prenatal exposure to air pollution on the occurrence of immune thrombocytopenia (ITP) in children Materials and Methods: This is a nationwide, population-based, matched case-control study. Using data from Taiwan’s Maternal and Child Health Database (MCHD), we identified 427 children with ITP less than 6 years of age and age-matched controls without ITP between 2004 and 2016. Levels of prenatal exposure to air pollutants were obtained from 71 Environmental Protection Administration monitoring stations across Taiwan according to the maternal residence during pregnancy. Patients who had outpatient visits or admission with diagnosis of ITP and subsequently received first-line treatment of intravenous immunoglobulin or oral glucocorticoids were defined as incidence cases. Results: Prenatal exposure to particulate matter < 10μm (PM10) in diameter and the pollutant standard index (PSI) increased the risk of childhood ITP. Conversely, carbon monoxide (CO) exposure during pregnancy was negatively associated with the development of ITP. Conclusion: Certain prenatal air pollutant exposure may increase the incidence of ITP in children.